The Relationship of Husband and Wife in The Perspective of Mubadalah: Is A Study of The Concept of Rights and Obligations According To KH. Hasyim Asy'ari - Isyaq Maulidan; Mukhtar Adinugroho (Journal of Islamic Civilization, 2023)
The concept of rights and obligations in the Book of Ḍau' Al-Miṣbaḥ Fī Bayāni Aḥkām Al-Nikāh by KH Hasyim Asy'ari refers to the textual meaning of hadith and refers to the social conditions at that time, so that the resulting understanding is gender biased. Meanwhile, nowadays the relationship between husband and wife has become a global issue. So how do you communicate this understanding so that it can be in line with current developments? The content analysis procedure used in this research method consists of four steps, namely data procurement, data reduction, inference and data analysis. In the Mubādalah principle, marriage is an agreement between a man and a woman to live together in one bond, working together to manage household roles. Because marriage is an agreement to live together, the pillars consist of five things, namely: Mitsaqan Ghalizan, Zawaj, namely partnership and togetherness, Taraadhin, Mua'syarah bil Ma'ruf, treating each other well and appropriately, Deliberation. The Mubadalah approach in reading the concept of the rights and obligations of husband and wife provides a progressive understanding and placing the relationship between husband and wife on an equal footing in both the private and public realms can provide an understanding of mutuality.